2011
DOI: 10.1002/jcb.23206
|View full text |Cite
|
Sign up to set email alerts
|

Metformin stimulates osteoprotegerin and reduces RANKL expression in osteoblasts and ovariectomized rats

Abstract: Anti-diabetic drug metformin has been shown to enhance osteoblasts differentiation and inhibit osteoclast differentiation in vitro and prevent bone loss in ovariectomized (OVX) rats. But the mechanisms through which metformin regulates osteoclastogensis are not known. Osteoprotegerin (OPG) and receptor activator of nuclear factor κB ligand (RANKL) are cytokines predominantly secreted by osteoblasts and play critical roles in the differentiation and function of osteoclasts. In this study, we demonstrated that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
136
3
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(154 citation statements)
references
References 24 publications
8
136
3
7
Order By: Relevance
“…In agreement with those results, adiponectin was demonstrated to inhibit the stimulation by tumour necrosis factor a and RANKL of the master transcriptional factor of RANKL-induced osteoclastogenesis, the nuclear factor of activated T cells c1, through the AMPK signaling pathway . Metformin was very recently shown to reduce osteoclast differentiation and activity by stimulating osteoprotegerin (OPG) and inhibiting RANKL mRNA and protein expression in osteoblasts (Mai et al 2011). Conflicting results were however shown by Quinn et al (2010) who demonstrated that AICAR treatment in male mice stimulates bone loss and bone turnover with elevated rates of both bone formation and bone resorption (Quinn et al 2010).…”
Section: Effect Of Ampk Activation On Bone Cell Activities In Vitro Amentioning
confidence: 99%
See 3 more Smart Citations
“…In agreement with those results, adiponectin was demonstrated to inhibit the stimulation by tumour necrosis factor a and RANKL of the master transcriptional factor of RANKL-induced osteoclastogenesis, the nuclear factor of activated T cells c1, through the AMPK signaling pathway . Metformin was very recently shown to reduce osteoclast differentiation and activity by stimulating osteoprotegerin (OPG) and inhibiting RANKL mRNA and protein expression in osteoblasts (Mai et al 2011). Conflicting results were however shown by Quinn et al (2010) who demonstrated that AICAR treatment in male mice stimulates bone loss and bone turnover with elevated rates of both bone formation and bone resorption (Quinn et al 2010).…”
Section: Effect Of Ampk Activation On Bone Cell Activities In Vitro Amentioning
confidence: 99%
“…While the authors of this study confirmed that AICAR stimulates osteoclast formation in vitro, a result in contradiction with the previously mentioned in vitro studies demonstrating that AMPK activation suppresses osteoclast activity, they however showed that AICAR's effect was independent of AMPK signaling (Quinn et al 2010). The effect of metformin on bone mass in vivo was also poorly studied, but two recent studies indicate that metformin reduces the bone loss induced by ovariectomy (OVX), in part through increasing bone formation via induction of osteoblast genes such as Runx2 and Lrp5 (Gao et al 2010) and by reducing RANKL and stimulating OPG expression in osteoblasts (Mai et al 2011).…”
Section: Effect Of Ampk Activation On Bone Cell Activities In Vitro Amentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have indeed shown that TZDs increase fracture risk (10,11). In contrast, metformin, another widely prescribed anti-diabetic drug (12), is osteogenic in vitro (13,14) and reduces the risk of fracture in DM patients (15), as well as inhibiting the bone loss induced by ovariectomy (OVX) in rats (16,17). However, our recent studies showed no beneficial effect of metformin on bone mass and fracture healing in rodents (18).…”
Section: Introductionmentioning
confidence: 99%